2023
DOI: 10.1021/acs.jafc.3c06863
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin Isomers: A Comprehensive Review of Isomerization Methods and Analytic Techniques

Xiaojuan Liu,
Lesong Zhou,
Junting Xie
et al.

Abstract: The presence of multiple conjugated double bonds and chiral carbon atoms endows astaxanthin with geometric and optical isomers, and these isomers widely exist in biological sources, food processing, and in vivo absorption. However, there remains no systematic summary of astaxanthin isomers regarding isomerization methods and analytic techniques. To address this need, this Review focuses on a comprehensive analysis of Z-isomerization methods of astaxanthin, including solvent system, catalyst, and heat treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 103 publications
(246 reference statements)
0
1
0
Order By: Relevance
“…Astaxanthin, a carotenoid mainly found in shrimp, crab, fish, and microalgae with potent antioxidant properties and numerous health benefits, has garnered significant interest. , Similar to other carotenoids, its Z -configuration, particularly 9- Z -astaxanthin, displays superior biological functions to the all- E -isomer. For example, studies have shown that Z -astaxanthin has enhanced anti-inflammatory properties. Our prior experiments have solidified the role of CD36 as the principal transporter protein facilitating astaxanthin absorption at dietary concentrations .…”
Section: Introductionmentioning
confidence: 99%
“…Astaxanthin, a carotenoid mainly found in shrimp, crab, fish, and microalgae with potent antioxidant properties and numerous health benefits, has garnered significant interest. , Similar to other carotenoids, its Z -configuration, particularly 9- Z -astaxanthin, displays superior biological functions to the all- E -isomer. For example, studies have shown that Z -astaxanthin has enhanced anti-inflammatory properties. Our prior experiments have solidified the role of CD36 as the principal transporter protein facilitating astaxanthin absorption at dietary concentrations .…”
Section: Introductionmentioning
confidence: 99%